The monitoring and evaluation of NPOs by the Department of Social Development Northern Cape - Monyane, Thabiso Joseph (University of the Free State, 2014)
The primary objective of this study was to determine whether the Department of Social Development in the Northern Cape Province implemented effective monitoring and evaluation at Non-profit Organisations. The study was prompted by the high levels of non-compliance by NPO‟s with the reporting requirements as set out in the Non-Profit Organisation Act, Act 71 of 1997. Due to these high levels of non-compliance, majority of NPO‟s were deregistered. The deregistration simply meant that these entities may no longer operate as such and may also not request financial assistance using the NPO certificate thus leaving the poor who depend on social service from these organisation with no protection against poverty. Using qualitative method, the research aimed to determine whether the department implemented effective M&E at NPO‟s. Data was collected during focus groups conducted with both NPO‟s and officials from the department. Responses from participants were narrated and classified into different categories using research questions as a guide. The classification was critical in determining common themes or common responses from the same research question and therefore determining dominance. The results indicated that no evaluation took place and that the current monitoring implemented was not effective. Stakeholders were not identified in the M&E process and therefore not involved in determining what must be monitored, evaluated, how, the frequency, etc. A participatory M&E is recommended for implementation by the department. This M&E system involves stakeholders and beneficiaries‟ participation in determining M&E objectives, what must be monitored, evaluated, how, frequency, etc. The M&E tool used must be aligned to the logframe. Objectives must be clearly identified and capacity levels at both NPO‟s and departmental officials improved.
Keywords: Monitoring; Evaluation; Effectiveness; Participatory M&E; Non-profit Organisation; Positive bias; Corruption in M&E; Stakeholders; Social Development; Deregistration; Logframe; Dissertation (MBA (Business Administration))--University of the Free State, 2014